2022
DOI: 10.3389/fnins.2022.989295
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of miRNA-modified mesenchymal stem cell extracellular vesicles in spinal cord injury: A systematic review of the literature and network meta-analysis

Abstract: BackgroundAlthough some previous studies have indicated that extracellular vesicles (EVs) secreted from miRNA-modified mesenchymal stem cells (MSCs) may be more effective as compared with control EVs in the treatment of rats with spinal cord injuries (SCI), the efficacy of this treatment modality remains controversial.ObjectivesThe current study comprehensively evaluated the efficacy of different administered doses of EVs, including miRNA-overexpressing MSCs-derived EVs, among SCI rats. The efficacy of EVs' tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
2
4
0
Order By: Relevance
“…Indeed, one proposed treatment effort is the delivery of engineered extracellular vesicles (EV's) containing a cocktail of miRNA's and enzymes to alter DNA methylation, histone modifications, and posttranscriptional modification (Gupta et al., 2023) after SCI. One recent meta‐analysis assessing the efficacy of miRNA associated EV delivery to promote recovery was efficacious in improving hindlimb motor function if delivered within 2 weeks of injury (Yang et al., 2022), which aligns with our observed heightened BDNF expression levels and improved functional recovery after 2 weeks observed here.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, one proposed treatment effort is the delivery of engineered extracellular vesicles (EV's) containing a cocktail of miRNA's and enzymes to alter DNA methylation, histone modifications, and posttranscriptional modification (Gupta et al., 2023) after SCI. One recent meta‐analysis assessing the efficacy of miRNA associated EV delivery to promote recovery was efficacious in improving hindlimb motor function if delivered within 2 weeks of injury (Yang et al., 2022), which aligns with our observed heightened BDNF expression levels and improved functional recovery after 2 weeks observed here.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, administration of MSC‐exosomes overexpressing miR‐126 markedly suppressed microglial activation as well as the production of inflammatory mediators in a rat model of stroke 150 . Confirming these results, other studies have demonstrated the significant protective effects of exosomes derived from miR‐modified MSCs by suppressing inflammatory pathways in the CNS 151–153 …”
Section: Mesenchymal Stem Cells and Msc‐derived Exosomes Regulate Neu...supporting
confidence: 68%
“…150 Confirming these results, other studies have demonstrated the significant protective effects of exosomes derived from miR-modified MSCs by suppressing inflammatory pathways in the CNS. [151][152][153] In sum, the transplantation of MSCs and their exosomes can provide an effective and safe nonpharmaceutical treatment for CNS diseases via the regulation of neuroinflammation.…”
Section: Mesenchymal Stem Cells and Msc-derived Exosomes Regulate Neu...mentioning
confidence: 99%
“…Some extensively used modification techniques include click chemistry‐based strategies for EV surface labelling using fluorescent beads, quantum dots, and supermagnetic particles, as shown in Figure 2. Studies indicate that MSC‐EVs have shown substantial therapeutic potential in various disease conditions without any modification (Chen et al., 2023, Rani et al., 2015, Yang et al., 2023, Zeng et al., 2022). However, these EVs are often complemented with specific formulations, adhesives, or hydrogels to increase their intrinsic therapeutic efficiencies (Liu et al., 2023, Wang et al., 2023).…”
Section: Ev‐engineering and Drug‐loading Strategies For Ev‐mediated D...mentioning
confidence: 99%